A study of perceived and preferred teaching styles in learning English language / Asliza Ahmad - Ahmad, Asliza (2012)
Most of the teachers have their own styles and methods of teaching the students. This study aims to identify the teaching styles of English language teachers that contribute to students' performance. This study examines the students' preference teaching styles with respect to their teachers' teaching styles. Besides, this study investigates the level of students' satisfaction of learning English in respect of their teachers' teaching styles. The teaching styles mentioned are based upon Grasha's Model (1996) consisting of Formal Authority, Demonstrator, Delegator and Facilitator Teaching Style. It has been done towards 169 pupils (random sampling) and four English teachers of a primary school in rural area through a survey method and interviews. The data gathered has been analyzed using SPSS. The findings revealed that, the teachers combined Demonstrator and Facilitator Teaching Styles in delivering the subject content. The result also demonstrated statistically significant higher scores in term of preference Formal Authority Teaching Style. In term of pupils' satisfaction level towards teacher's teaching styles in learning English, Demonstrator and Facilitator Teaching Style score higher than the others. Keywords: Teaching Styles, Achievement, Preferences, Satisfaction.